Amplitude modulation of anomalously reflected terahertz beams using all-optical active Pancharatnam–Berry coding metasurfaces. Issue 12 (13th March 2019) - Li, Jie; Zhang, Yating; Li, Jining; Yan, Xin; Liang, Lanju; Zhang, Zhang; Huang, Jin; Li, Jiahui; Yang, Yue; Yao, Jianquan
Abstract : Optical active Pancharatnam–Berry coding metasurfaces for amplitude modulation of terahertz beams. Abstract : Pancharatnam–Berry (P–B) metasurfaces introduce geometric phases to circularly polarized electromagnetic waves through geometric rotation of the unit cells, thereby converting spin angular momentum (SAM) to orbital angular momentum (OAM) of photons and achieving flexible modulation of spin-polarized waves. It is highly desirable for dynamically tunable P–B metasurfaces to be actively applied. Here, combining double split-ring resonators (DSRRs) with photosensitive semiconductor germanium (Ge), we propose three types of all-optical active Pancharatnam–Berry coding metasurface for dynamic amplitude modulation of spin waves and vortex beams in the terahertz band. Coupled with signal processing methods such as the convolution operation, optical active P–B coding metasurfaces show a strong regulation effect on terahertz beams. This opens up a broad path for coding metasurface applications such as high-speed wireless terahertz communications.